Students' Perception on the Use of 'Writing 3' Materials to Prepare Final Project Report Writing - Isnaini Nur Safitri; Pritantina Yuni Lestari; Prima Beauty Kartikasari (Jurnal Pendidikan Bahasa, 2022)
This paper aims to identify the second-year undergraduates’ perceptions on their experience in an academic writing course, ‘Writing 3’. This is the advanced writing module offered in the fourth semester after they completed ‘Writing 1’ and ‘Writing 2’. The research was conducted at the English Department of State Polytechnic of Malang. The study used a mixed method as the approach. First, it used a survey method towards approximately 42 English-major students from Diploma 3 of English for Translation and Hospitality Industry. Then, it was followed by a written interview with students. The results reveal that the students have good perception in the use of ‘Writing 3’ materials. The materials are also beneficial for them in preparing their final report writing and meet their need for scientific writing topics. Moreover, the components of each chapter/topic helped the students to write the report precisely since the materials are taken from the trusted resources and the exercises given helped them to explore their writing ability. It also shows that the students understand language features and format in each part in scientific writing.